ASSOCIATION BETWEEN LOW SERUM MAGNESIUM LEVEL AND TYPE 2 DIABETES MELLITUS IN ABBOTTABAD - Noor, Mohammad Munir; Nazir, Quratulann; Khan, Tariq Mehmood; Gillani, Saima; Abbasi, Munir Ahmad; Rauf, Abdur; Qureshi, Zaheer Uddin (Journal of Ayub Medical College Abbottabad, 2019)
Background: Magnesium serves as a cofactor for various oxidation reactions in the body and helps in glucose transport across cell membrane. Deficiency of magnesium is a common electrolyte abnormality in type 2 diabetic patients and is linked to development of various diabetic complications. This study was conducted to determine the association between low serum magnesium level and type 2 diabetes mellitus presenting at Medical B ward, BBS Hospital Abbottabad. Methods: This descriptive study was conducted over a period of 6 months starting July 1, 2017. One hundred & eighty diagnosed diabetic patients aged at least 40 years, were included in the study. Their serum magnesium level was checked after withdrawing blood under strict aseptic conditions. Fasting & random blood glucose and the level of glycosylated haemoglobin were measured and age, gender, duration of illness were recorded on a proforma. RESULTS: Sixty-one patients (33.89%) had hypomagnesemia. There was no significant association between hypomagnesemia and age and sex of patients (p>0.05). However, hypomagnesemia was found to be significantly associated with the duration of diabetes mellitus among study population (p=0.02). Conclusion: Hypomagnesemia is frequently present in patients with diabetes mellitus and it appears that its prevalence increases with the duration of diabetes mellitus. Keywords: Type 2 Diabetes Mellitus; Serum Magnesium levels; electrolyte disturbance; HbA1C